Survey Response Analysis on the Use of Environmental Data for Sports Information Systems Development - Dewi Arianti Wulandari; Wandy Wandy (Jurnal Teknologi, 2023)
Sport is primarily a mental and physical activity focused on competition with oneself, others, or the elements of nature—the contribution of sport to the modern world's social development, the nation, and the state. As history has shown, technical advancements have never diminished sports and linked to civilization's advancement in human life. Walking and bicycling are increasingly promoted as active modes of transportation and boosting physical activity levels. The elevated breathing rates in traffic microenvironments have generated worries about increased exposure to ultrafine particles. Amateur half marathoners did detrimental significantly when the temperature, heat index, and ozone levels rise. The athlete or recreational sportsperson can earn environmental information through several channels and devices. There are applications and widgets now embedded or separated from the device operating systems. This research aimed to find appropriate environmental information from recreational sportspeople's understanding and awareness of the environment's effect on sports performance. Walking (77) and running (48) were the most sports activities picked by the respondents. Then 99 (73%) respondents used environmental data before exercising. Weather (118) was the respondents' choice, followed by the temperature (47) and the air quality (30) picked by the respondents. Most respondents (72%) get environmental information from their smartphones, and 27 (18%) get it from the website. Environmental factors may impact sports activity performance, and the respondents used environmental information before the sports activities began. This research will later support the sports information system web application.